La calidad de servicio y su influencia en la satisfacción de los contribuyentes de la administración tributaria - SATT año 2015 - Robles Solórzano, Alessandra Ximena (2017)
The present research work developed with the purpose of demonstrating the Service Quality and its Influence on Taxpayer Satisfaction of the Tax Administration - SATT year 2015 ". The research problem is related to the following question: ¿How does the quality of service affect the satisfaction of taxpayers of the Tax Administration-SATT year 2015, Highlighting as a study variable: independent variable: Quality of Service; and dependent variable: Taxpayer Satisfaction. The population under study was made up of 94865 taxpayers from the Tax Administration -SATT year 2015, from which a representative sample of 386 taxpayers was established. This research was developed with a descriptive Transectional investigation design. In this way the methods applied were Deductive – Inductive, Analytical, Synthetic, Statistical and finally the following research techniques were applied: observation and questionnaire. From the obtained results, the outstanding results are that the taxpayers perceive the quality service, in general, as an average service quality and the taxpayers satisfaction level is in an average level as well. Besides, it was possible identify the Tangibles elements as the highest scored dimension and the Response Capability as the lowest scored dimension. The investigation concluded that the quality of service has a significantly influence on the satisfaction of taxpayers of the Tax Administration - SATT year 2015, information that is verified through the application of the chi square method, which yields a result of 272.85 and The V of Cramer that yields a result of 0.56.